GLOCALIZATION OF WALI SONGO ISLAMIZATION IN 15TH – 16TH CENTURIES - Nurul Hak (2024)
Wali Songo’s Islamization has been identical to the Islamization of the Island of Java. This assumption, however, holds as if Wali Songo’s venture was confined locally to Java while such a process encompassed the Archipelago and beyond. This article aims to reconstruct the Wali Songo's Islamization from glocalization perspective, by involving both local and global phenomenon of the Islamization processes.To further analyze the Islamization, this study uses geo politics and cultural diffusion theories. Data in this study was collected using historical methods consisting of heuristics, source criticism, interpretation, and historiography. The results of this study showed two findings. First of all that Wali Songo Islamization constituted cosmopolitan Islam, indicated by process of Wali Songo Islamization that was not only local Java but also regional (Nusantara) and global ones.Wali Songo Islamization of local Java took the micro areas of the preaching and spreading Islam in the region, including East Java, Central Java and West Java. While the Islamization of regional and global took macro areas as the networking strategies of the preaching Islam in the region, indicated by the integration between global and local (glocalization) processes of the Islamization. Second, the glocalization of Wali Songo Islamization could be understood by emplacing the Islamization as World History of Islam in Medieval Period using multi-perspectives.